The accuracy of linear and angular measurements in the different regions of the jaw in cone-beam computed tomography views - Mehrdad Abdinian; Homa Baninajarian (Wolters Kluwer Medknow Publications, 2017)
Introduction: The use of cone-beam computed tomography (CBCT) has increased lately. The aim of this study was to evaluate the accuracy of linear and angular measurements by CBCT in the different areas of the jaws. Materials and Methods: In this study, the mesiodistal width and height as well as the angular measurements were ascertained in four different sites of the mandibular and maxillary jaws (anterior, canine, premolar, and molar regions). Each area was outlined by gutta-percha as opaque markers. The measurements were obtained by a digital caliper (as gold standard) and on CBCT views including "three-dimensional" and "panaroma" (section thickness of 5 and 10 mm). Data were analyzed by the one-way analysis of variance (ANOVA). Results: The means [standard deviation (SD)] of measurement accuracy of all groups were more than 90%. There was no significant difference between the means (SD) of measurement accuracy of all views (oneway ANOVA, P > 0.05). The means (SD) of measurement accuracy of all views in four regions of the jaws had no significant difference (one-way ANOVA, P > 0.05). Conclusion: This study showed that CBCT imaging has a high degree of measurement accuracy in all three horizontal, vertical, and angular measurements as well as the "panorama" (5- and 10-mm thicknesses) and "three-dimensional" views in all the areas of the jaws. Therefore, the use of CBCT in the linear and angular measurements of the dentomaxillofacial region can be recommended.